An unsymmetrical binuclear iminopyridine-iron complex and its catalytic isoprene polymerization. Issue 62 (7th July 2020) - Wang, Liang; Wang, Xiaowu; Hou, Hongbin; Zhu, Guangqian; Han, Zhenyu; Yang, Weiying; Chen, Xiao; Wang, Qinggang
Abstract : A series of chloride-bridged unsymmetrical Fe(ii )-HS/Fe(ii )-LS binuclear complexes has been developed, which can efficiently catalyze isoprene polymerization with 0.00025 mol% loading, delivering ultra-high molecular weight polymers. Abstract : A series of chloride-bridged unsymmetrical mixed Fe(ii )-HS/Fe(ii )-LS binuclear structures has been prepared and characterized. Upon activation with MAO, highly efficient catalytic polymerization of isoprene was achieved, delivering an ultra-high molecular weight (catalyst loading = 2.5 ppm, M n = 1.8 × 10 6 g mol −1, M w / M n = 1.4).